Malignant ilnesses in men breast. A twenty-five year study - Lidia Torres Ajá (Medisur)
Background: Breast tumors prevailed in female population, nevertheless in male population appear although it is very infrequent to be found. Objective: to describe the clinical-pathologic behavior of breast cancer in Cienfuegos province. Method: A descriptive-retrospective study of breast tumors in males who were surgically treated at the University Hospital ";Dr. Gustavo Aldereguía Lima” in Cienfuegos, Cuba from January 1st 1981 to December 31st 2005. The variables used were the following: age, affected breast, topographic localization of the tumor, clinical stage at the time of diagnosis, histological variant, type of biopsy used for this purpose, surgical technique applied, and health area belonging to. Results: male breast cancer represented the 0.8 % out of the total of breast cancers which were surgically treated during this studied period. Detection at very advanced clinical stages was confirmed. Conclusions: It is necessary to establish mechanisms for their early detection due to the increment in the incidence of this disease in males.